Hepatic uptake of conjugated bile acids is mediated by both sodium taurocholate cotransporting polypeptide and organic anion transporting polypeptides and modulated by intestinal sensing of plasma bile acid levels in mice - Slijepcevic, Davor; Blank, Antje (Hepatology, 2017)
The Na+-taurocholate cotransporting polypeptide (NTCP/SLC10A1) is believed to be pivotal for hepatic uptake of conjugated bile acids. However, plasma bile acid levels are normal in a subset of NTCP knockout mice and in mice treated with myrcludex B, a specific NTCP inhibitor. Here, we elucidated which transport proteins mediate the hepatic uptake of conjugated bile acids and demonstrated intestinal sensing of elevated bile acid levels in plasma in mice. Mice or healthy volunteers were treated with myrcludex B. Hepatic bile acid uptake kinetics were determined in wild-type (WT), organic anion transporting polypeptide (OATP) knockout mice (lacking Slco1a/1b isoforms), and human OATP1B1-transgenic mice. Effects of fibroblast growth factor 19 (FGF19) on hepatic transporter mRNA levels were assessed in rat hepatoma cells and in mice by peptide injection or adeno-associated virus-mediated overexpression. NTCP inhibition using myrcludex B had only moderate effects on bile acid kinetics in WT mice, but completely inhibited active transport of conjugated bile acid species in OATP knockout mice. Cholesterol 7α-hydroxylase Cyp7a1 expression was strongly down-regulated upon prolonged inhibition of hepatic uptake of conjugated bile acids. Fgf15 (mouse counterpart of FGF19) expression was induced in hypercholanemic OATP and NTCP knockout mice, as well as in myrcludex B-treated cholestatic mice, whereas plasma FGF19 was not induced in humans treated with myrcludex B. Fgf15/FGF19 expression was induced in polarized human enterocyte-models and mouse organoids by basolateral incubation with a high concentration (1 mM) of conjugated bile acids. Conclusion: NTCP and OATPs contribute to hepatic uptake of conjugated bile acids in mice, whereas the predominant uptake in humans is NTCP mediated. Enterocytes sense highly elevated levels of (conjugated) bile acids in the systemic circulation to induce FGF15/19, which modulates hepatic bile acid synthesis and uptake. (Hepatology 2017;66:1631-1643).
Gesehen am 18.10.2018